Transferências fiscais intergovernamentais no Brasil: Uma avaliaç\~ao das transferências federais, com ênfase no sistema único de saúde - Angelo José Mont'Alverne Duarte; Alexandre Manoel Angelo da Silva; Everaldo Manoel Luz; José Carlos Gerardo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– On this paper, we evaluate the Brazilian intergovernmental fiscal transfers, identifying which kind would be more adequate to schedule a transfer system denoted by efficiency and equity in the access to public services, proposing, in particular, specifics kind and ways of executing healthcare programs. After empirical analysis, based on 2006, it suggests that the real schedule have not contemplated transfers focused on output and outcome. Besides, it suggests that the federal government has not utilized equity criteria in the access to healthcare public services.
Keywords: H71; H77; 330; Finanzausgleich; Brasilien